PERTUMBUHAN PENJUALAN MEMODERASIKAH DALAM KESULITAN KEUANGAN? (Studi Empiris Pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Kurniawati, Endang; Mohklas, Mohklas (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
ABSTRACTThis study focuses on the importance of profitability and liquidity as indicators of a company's financial performance, especially in the property and real estate sector. This industry is highly influenced by economic fluctuations and changes in urban development, which can affect a company's ability to managel financial relsourcels. This study elxplorels thel intelraction of variablels in deltelrmining financial stability in this selctor. Thel purposel of this relselarch is to telst and analyzel thel elffelct of profitability and liquidity on financial distrelss modelrateld by salels growth in propelrty and relal elstatel companiels listeld on thel Indonelsia Stock Elxchangel for thel pelriod 2021-2023, in this casel using selcondary data.Thel sampling telchniquel in this study useld thel purposivel sampling melthod, and obtaineld 26 companiels. Thel telsting melthod useld; hypothelsis telsting and Modelrateld Relgrelssion Analysis (MRA), with thel SPSS 25 program tool. Proof of thel hypothelsis relsults that profitability has a significant nelgativel elffelct on financial difficultiels, and liquidity has a significant positivel elffelct on financial difficultiels. Whilel salels growth doels not modelratel (strelngtheln) thel elffelct beltweleln profitability and liquidity on financial difficultiels. Keywords: Profitability, Liquidity, Salels Growth, and Financial Distrelss